Security and the Networked Society - Gregory, Mark A.; Glance, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book examines technological and social events during 2011 and 2012, a period that saw the rise of the hacktivist, the move to mobile platforms, and the ubiquity of social networks. It covers key technological issues such as hacking, cyber-crime, cyber-security and cyber-warfare, the internet, smart phones, electronic security, and information privacy. This book traces the rise into prominence of these issues while also exploring the resulting cultural reaction. The authors$1 (Banalysis forms the basis of a discussion on future technological directions and their potential impact on society. The book includes forewords by Professor Margaret Gardner AO, Vice-Chancellor and President of RMIT University, and by Professor Robyn Owens, Deputy Vice-Chancellor (Research) at the University of Western Australia. Security and the Networked Society provides a reference for professionals and industry analysts studying digital technologies. Advanced-level students in computer science and electrical engineering will also find this book useful as a thought-provoking resource.s
Introduction -- Hacking -- Cyber Crime, Cyber Security and Cyber Warfare -- Internet -- Smart Phones -- Applications -- Predictions.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Information systems; Computer Science; Information Systems and Communication Service; Systems and Data Security; Computer Communication Networks; Data Encryption; Information Systems Applications (incl. Internet).